ISLAMIC SOCIAL FINANCE AS A CATALYST FOR INCLUSIVE AND SUSTAINABLE DEVELOPMENT: INTEGRATING ZAKAT, WAQF, AND ISLAMIC ECONOMIC PRINCIPLES - Siti Habibatur Rahma; Siti Shoimatul Azizah (International Conference on Humanity Education and Society (ICHES), 2026)
Sustainable development requires a development framework that balances economic growth, social justice, inclusiveness, and long-term societal welfare. In this context, Islamic social finance, encompassing zakat and waqf, offers a normative and institutional mechanism based on the principles of redistribution and social responsibility. This study aims to analyze the role of Islamic social finance as a catalyst for inclusive and sustainable development through the integration of zakat and waqf within the Islamic economic system. This study uses an empirical approach by analyzing the contribution of zakat and waqf instruments to poverty alleviation and community economic empowerment. Data were obtained from institutional reports and community economic indicators, then analyzed descriptively and analytically. The results show that effective and integrated management of zakat and waqf can increase community income, strengthen community-based economic activities, and reduce poverty levels. This study concludes that Islamic social finance functions not only as a philanthropic instrument but also as a sustainable development model that supports inclusive economic growth and social transformation.